Molecular docking of several compounds in Bauhinia thonningii as alfa estrogen receptor inhibitors in breast cancer - Zaqia, Lulu; Alhestha, Salsabila Zahra; Rahmadini, Celina Fadila; Kusumawati, Maiya; Dhiya, Syifa Nasywa; Andriani, Wellen Putri; Azzahra, Zeta Agustri; Auli, Winni Nur; Saputro, Anjar Hermadi (Pharmacy Reports, 2023)
Compounds contained in Bauhinia thonningii have been proven in vitro to have anti-breast cancer effects. This research was carried out to validate in silico the compounds contained in Bauhinia thonningii. The molecular docking process begins with the ER target protein alpha (PDB id: 2BJ4) downloaded from the web http://www.rcsb.org/. After that, validation was carried out on natural ligands and target proteins using AutodockTools (Autodock 4.2 and Autogrid). Continued with optimization of the compounds to be tested, namely 6,8-Di-C-methyl kaempferol 3,7-dimethyl ether; 6-C-Methylquercetin-3,4'-dimethylether; Quercetin‑3‑O‑α‑L‑rhamnopyranoside and Tamoxifen as a positive control was downloaded at https://molview.org/ then geometrically optimized using Avogadro then docked with the target protein ER-α. Obtained bond energy results between natural ligands, 3 test compounds and 1 control compound 4-HYDROXYTAMOXIFEN; 6,8-Di-C-methyl kaempferol 3,7-dimethyl ether; 6-C-Methylquercetin-3,4'-dimethylether ;Quercetin-3–O-α-L-rhamnopyranoside and tamoxifen were -11.32,-6.07, -7.26,-8.88, -10.33 kcal/mol. If we look at the smallest bond energy, it is found that the compounds that have the greatest potential when sorted are the natural ligand, positive control, Quercetin‑3‑O‑α‑L‑rhamnopyranoside, 6-C-Methylquercetin-3,4'-dimethyl ether and 6,8-Di-C-methyl kaempferol 3,7-dimethyl ether.